Улогата на физикалната терапија и рехабилитација во лекувањето на пациентите со примарна остеопороза - Коевска, Валентина (Медицински факултет, УКИМ, Скопје, 2016)
Osteoporosis is а multifactorial progressive skeletal disorder characterized by reduction in bone mass and deterioration of bone microarchitecture, predisposing to increased fracture risk. These fractures are very often associated with morbidity, mortality, loss of physical function and high economic costs. Over the last decade, in addition to pharmacotherapy, physical therapy and rehabilitation have been developed and became quite important as non-pharmaceutical treatment, which comprises different exercises and physical modalities. Hence, a need for clinical study presenting the current experiences with physical therapy and rehabilitation in our country has emerged. The main goals of the study were: to examine demographic and anthropological characteristics of patients with primary osteoporosis, to analyze biochemical parameters, to evalute the efficiency of physical agents in pain treatment, to assess the efficiency of exercises in improvement of bone mineral density and to evaluate the quality of life of patients with primary osteoporosis before and after one year of physical therapy and rehabilitation. In our prospective study, conducted from March 2015 to September 2016, a total of 92 women with primary osteoporosis were included, randomly divided in three groups. The first group received physical agents and practiced osteoporosis exercises; the second group practiced only exercises and the third group comprised patients who did not practice exercises. During the entire trial period the patients received bisphosphonate therapy. All patients signed an informed consent for taking part in the study. Numerical pain scale was applied for pain assessment. BMD was determined by dual-energy x-ray absorptiometry. The Qualeffo-41 Questionnaire was used for measuring quality of life. The follow-up period of patients was one year. The results have shown that deformity was present in 83.69% of patients, while 58.69% of them had kyphosis. After one year the biochemical results have shown a significant decrease in β-crosslaps (p<0.001), substantial increase in the average vitamin D in the blood (p<0.001). The pain was significantly reduced in the first and the second group as compared to the third group of patients (p=0.0029). There was no significant difference of BMD results between the groups for lumbar spine (p=0.72) and for femoral neck (p=0.056), while there was a signficant difference in the results of the t-score between the groups for lumbar spine (p=0.04) and for femoral neck (p=0.018). The results obtained with the Qualeffo-41 Questionnaire showed a significant statistical difference between the groups (p<0.0001) regarding pain, physical activity, social life, perception of own health, but not regarding mental functioning (p<0.3). CONCLUSION: Applied physical agents and exercises after one year significantly reduced the pain and improved patients’ life quality as well as t-score in the first and the second groups in comparison with the third group. It is an undisputable role of physiotherapy and rehabilitation in the prevention and treatment of patients with primary osteoporosis.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Снежана Мишевска Перчинкова.
Keywords: primary osteoporosis, exercises, physical agents, t result, life quality